2018
DOI: 10.3389/fvets.2018.00134
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of ORF Viruses From Five Contagious Ecthyma Outbreaks in Argentinian Goats

Abstract: Orf virus (ORFV) is the etiological agent of Contagious Ecthyma (CE) disease that mainly affects sheep, goats, wild ruminants, and humans with a worldwide distribution. To date, only two strains from Argentinian sheep have been characterized at the molecular level and there is little information on ORFV strains circulating in Argentina. Here we describe and analyze five outbreaks of CE in goats in three geographic regions of the country: Northwest, Center, and Southwest. The phylogenetic analysis based on four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
(41 reference statements)
3
17
0
Order By: Relevance
“…No human case of infection was observed in the present outbreak. Similar to the earlier reports [4,5,7], PCR is the ideal test for the confirmatory diagnosis of Orf viral outbreak in the present study also.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…No human case of infection was observed in the present outbreak. Similar to the earlier reports [4,5,7], PCR is the ideal test for the confirmatory diagnosis of Orf viral outbreak in the present study also.…”
Section: Resultssupporting
confidence: 90%
“…This epitheliotropic virus is hardy in nature and could remain viable for months or even years in conducive environment, and the transmission of this virus commonly happens through contact from infected to susceptible animals [2]. In spite of the easy diagnosis of Orf disease based on the clinical symptoms, final confirmation was done using the molecular diagnostic approach of polymerase chain reaction (PCR) studies [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Since those two municipalities are separated by more than 200 km, there is no other possibility of the virus spreading between them in the field expect by means of stock movement via traded animals. This conclusion could be concurred with recent study which showed that the virus can be introduced into a herd with new asymptomatic infected animals (Peralta et al, 2018). For isolation of ORFV, primary lamb testes cell culture is most commonly used because of its high sensitivity (Kottaridi et al, 2006).…”
Section: Discussionsupporting
confidence: 84%
“…In Serbia, ORFV infection in humans and ruminants other than sheep and goats has never been reported. Proliferative crust lesions as pathognomonic clinical signs of ORFV infection could be found in the area of lips, nostrils, mouth, udder, and foot (Maganga et al, 2016;Peralta et al, 2018). There are many other diseases causing similar proliferative lesions, including Foot and mouth disease (FMD) (FitzGerald et al, 2015), Bluetongue (Backx et al, 2007), Peste des petits ruminants (OIE, 2013) and Sheep pox (OIE, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Lesions on the udder and foot can prevent the offspring from feeding as well as transient lameness [3,4].…”
Section: Introductionmentioning
confidence: 99%